Natal territory size, group size, and body mass affect lifetime fitness in the cooperatively breeding Florida Scrub-Jay. (20th May 2015) - Mumme, Ronald L.; Bowman, Reed; Pruett, M. Shane; Fitzpatrick, John W.
Abstract: Early rearing conditions can have profound short- and long-term effects on survival and reproduction of vertebrates. In cooperatively breeding birds, where variable social conditions interact with other sources of environmental variation, fitness consequences of the natal environment are of particular interest. We used data from a long-term study of the Florida Scrub-Jay ( Aphelocoma coerulescens ) to examine how characteristics of the natal brood, territory, and social group interacted to influence future survival and reproduction. Nestling and juvenile body mass were significant positive predictors of survival from fledging through the first year of life. The area of oak scrub in the natal territory correlated positively with nestling and juvenile body mass and had two long-term consequences: it was positively related to the probability of becoming a breeder and negatively related to age at first breeding, particularly for males. Effects of natal group size were complex and partially dependent on territory size. Although positively associated with nestling mass and postfledging survival, the presence of helpers was negatively related to juvenile body mass, but only in territories with <8 ha of oak scrub, suggesting that helpers become competitors for food as juveniles in small territories reach independence. Although early-life environmental conditions had strong effects on nestling and juvenile body mass, survival to yearling stage, and acquisition of a breeding territory, early conditions were not significant predictors of survival or reproduction once breeding status was obtained. This result suggests that low-quality jays from poor natal environments are winnowed out of the pool of potential breeders by intense intraspecific competition, ultimately leading to low heterogeneity in breeder quality. Our findings help to resolve the long-standing question of why Florida Scrub-Jays defend such unusually large territories for their body size, revealing a key selective advantage for cooperative territorial defense in the evolution of cooperative breeding.